Formulation and substantiation of homemade complementary baby food by selective feeding trial - Hakim, Md. Abdul; Alam, Md. Ariful; Musa, Mohamed Hanafi; Rouf, Shaikh Md. Abdur; Alam, Md. Amirul; Sarker, Md. Zaidul Islam (WFL Publisher, 2013)
The complementary food was prepared from dried grinded corn, bengal gram and sesame seed, banana, pumpkin and sugar with adequate amount. The results indicated that the crude protein, lipid, fibre, ash, moisture, energy and carbohydrate were higher than values in the proprietary formula. To evaluate the efficacy of this low cost complementary baby food on the growth of children between the age group 1 to 2 years and intervention program was carried out in an urban slum. For this trial feeding 18 children with various degrees of malnutrition were selected from slum dwellers by anthropometric indices. The children were classified as control and feeding group. The anthropometric indices of these children showed that control group suffers from continuous weight loss where as the feeding group showed positive correlation with the growth curve. Thus, complementary food processed from locally available food commodities must have a great potential in providing nutritious foods.